2013
DOI: 10.1039/c3dt51632f
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Cp2M (M = Ni, V) with dilithium diamido-aryl reagents; retention and oxidation of the transition metal ions

Abstract: The reactions of dilithium 1,2-diamidobenzene, [1,2-(HN)2C6H4]Li2 (L(1)H2)Li2, and dilithium 1,8-diamidonaphthalene, [1,8-(NH)2C10H6]Li2 (L(2)H2)Li2, with Cp2Ni and Cp2V have been used to obtain the new complexes (L(2)H2)2Ni{Li(THF)2}2 (3), (L(2)H2)3V{Li(THF)2}3 (4) and (L(1)H2)6Ni6·{[(L(1)H2)3(L(1)H)3Ni6Li(THF)](2-)·2[Li(THF)4](+)} (5), in which retention or oxidation of the initial metal(ii) centre is observed. Whereas 3 and 4 contain one transition metal ion within ion-paired structures, 5 has a complicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[1][2][3][4] Spectroscopic methods indicated that many of these dimers exist as mixtures of isomers, which have been attributed to the substituents attached to the ring. [5][6][7][8][9][10][11][12][13][14][15][16][17] However, the M-L bonds within the dimeric core can be different in nature, which could impact the spectroscopic results as well. Meanwhile, the orbital interactions within the core vary depending on the distance between M atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Spectroscopic methods indicated that many of these dimers exist as mixtures of isomers, which have been attributed to the substituents attached to the ring. [5][6][7][8][9][10][11][12][13][14][15][16][17] However, the M-L bonds within the dimeric core can be different in nature, which could impact the spectroscopic results as well. Meanwhile, the orbital interactions within the core vary depending on the distance between M atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Dimeric metal complexes with an M 2 (μ-L) 2 (M: metal; L: bridging element) ring are common in chemistry. Spectroscopic methods indicated that many of these dimers exist as mixtures of isomers, which have often been attributed to the nature of the substituents attached to the ring. The M–L bonds within the dimeric core can also be different in their nature, which could impact the spectroscopic results. Meanwhile, orbital interactions within the core vary depending on the distances among the M and L atoms .…”
Section: Introductionmentioning
confidence: 99%
“…It is a coordinatively and electronically unsaturated molecule with intriguing reactivity, such as oxidative addition of unsaturated hydrocarbons or nitriles and cyclopentadienyl displacement reactions. [1][2][3][4][5] Unlike many other first-row metallocenes, [6][7][8] vanadocene has no structurally characterized complexes with N-heterocyclic carbenes (NHCs) or heavier low-valent group 14 homologues.…”
mentioning
confidence: 99%